El material didáctico en el desarrollo del lenguaje y comunicación en niños y niñas de 2 a 3 años de edad del CDI “Mushuk Pakari” provincia de Bolívar, ciudad de Guaranda, parroquia Vinchoa, en el año 2022 - Castro Ronquillo, Karen Brigitt (2022)
Language is the way that human beings use to be able to communicate with others, for this reason, our research work has perspective aimed at didactic materials in the development of language and communication in children from two to three years of age the CDI Mushuk Pakari, which has the objective of analyze the didactic material for the improvement of the language and communication in children. Our research work has a qualitative and quantitative approach, it will comply with an investigative design in terms of the variables; didactic material as independent variable and the improvement of language and communication a dependent variable. In the same way, we present our problem of investigation descriptively. The interview was used as a method, which was directed to the teacher and she manifested the little use that is given to didactic material and the little acquisition of language and communication that children lack, in the other hand, it was used the observation sheet, in which it was noticed that children have deficiency in language, communication and participation with others. Therefore, these methods used allowed us to reach and understand some conclusions and also have a proposal, which consists of the application and realization of didactic materials for the improvement of language and communication in children from two to three years of age of the CDI Mushuk Pakari